Democracia y política exterior : los casos de Argentina y Brasil - Russell, Roberto; Hirst, Mónica (Estudios Internacionales, 1987)
This work attempts to show that the continuity of the current Argentine foreign policy project is a variable dependent on the implementation of democracy. Likewise, an attempt is made to explain the deep link between this project and the specific requirements of a process, still fragile, of institutional strengthening. In the Brazilian case, we argue that its current foreign policy project presupposes the existence of democratic norms both at the domestic level and on the international scene. The articulation between Brazilian foreign policy and the democratic system is analyzed, at the domestic and international level during the last thirteen years. This is intended to verify the importance for this foreign policy in this period of the internal and external conditions linked to a "democratizing" project.